Islamic Outreach in the Digital Age: A Study of Online Dawah Practices in Taraba State, Nigeria - Ali, Bello (Fakultas Dakwah UIN KHAS Jember, 2025)
This study explores the transformative role of social media in Islamic religious outreach (Da’wah) within Taraba State, Nigeria. Using a quantitative descriptive approach, it analyzes the engagement patterns, content preferences, platform usage, and perceived spiritual impacts among 217 Muslim respondents. Findings reveal high daily engagement with Da’wah content on Facebook and WhatsApp, with audio-visual formats proving most effective. Online Da’wah significantly enhances religious knowledge, communication, and social cohesion, though gender disparities, infrastructural deficits, and content authenticity challenges remain. The paper offers thematic insights and practical recommendations aimed at enhancing digital Da’wah inclusivity, cultural sensitivity, and strategic dissemination. It underscores the potential of social media to serve as a dynamic and complementary tool to traditional Islamic propagation, provided that ethical standards and technological capacities are prioritized.